Topologically-crosslinked hydrogels based on γ-cyclodextrins - Ella Sapsford; Davide Michieletto (Communications Chemistry)
Abstract Biomimetic strategies are increasingly the focus of materials scientists looking to improve or invent new materials. Topology is an important component in nature, but the synthetic incorporation of mechanically interlocked moieties is challenging. Rotaxanes are one of the simplest ways to introduce topological complexity to a polymer gel. As mobile crosslinks, the rotaxane’s cyclic host molecules redistributes applied stress typically endowing the material with enhanced toughness and stretchability. Gamma-cyclodextrin (γ-CD) is a larger homologue of alpha-cyclodextrin (α-CD) and it allows uncommon double-threaded topologies to be synthesised without metal templating removing additional synthetic steps and toxicity. γ-CDs are good candidates for a slide-ring crosslinkers that, added to a commodity or novel polymer, could augment the mechanical properties of hydrogels in novel ways with respect to traditional polyrotaxanes and slide-ring gels (SRGs). Despite the rapid uptake of γ-CD as novel mechanical crosslinkers, the body of literature is currently limited. In this paper we thus review recent works on γ-CD functionalised materials, offer a comparison with α-CD materials, and compare the mechanical performance of the papers discussed in plots of material properties. Finally, we discuss potential directions and unique uses of γ-CD uncommon double-threaded topology.